Studi Penggunaan Media Filtrasi Pasir Silika, Manganese, Dan Arang Aktif Untuk Menurunkan Parameter Pencemaran TDS, Mangan, Nitrat (NO2) dan MPN Coliform Terhadap Kuliatas Air Sumur Gali di Kelurahan Patingalloang, Kecamatan Ujung Tanah, Makassar 2023 - Saswini, Andi Ade Ula; Yusriyanto, Yusriyanto; Syafri, Muh (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Introduction: site requirements for the construction of a dug well, this is necessary so that the quality of dug well water is safe in accordance with the established rules, Pollution caused by bacteria to water in the ground widens to ± 2 meters at a distance of 5 meters from the source of pollution 3 and narrows to a distance of 11 meters in the direction of the soil flow, Research Method: This type of research is descriptive research, namely to determine the use of silica sand filter media – activated carbon in filter reactors to reduce TDS, Nitrite (NO2), Dissolved Manganese and MPN Coliform with a comparison of the composition of filter media with references to clean water quality standards Permenkes No. 2 of 2023, The sample in this study is 1 dug well located in Pattingaloang Village, Ujung Tanah District, Makaasar City in 2023. Results: The results of this study after filtration interventions of manganese media, activated carbon, and silica sand found that TDS, color, Manganese Nitrite (NO3) has decreased environmental pollution levels in accordance with the Regulation of the Minister of Health of the Republic of Indonesia Number 2 of 2023. Conclusion: The conclusion of the research results is that silica, manganese and activated carbon sand filtration media, TDS, manganese (NO2) nitrate and MPN Coliform can effectively reduce water pollution levels in dug wells in accordance with Minister of Health Regulation No. 2 of 2023. So that the risk of infectious and non-communicable diseases can be overcome by the intervention of filtration media filtration of silica sand, manganese and activated carbon.